2007
DOI: 10.1093/hmg/ddm132
|View full text |Cite
|
Sign up to set email alerts
|

Non-synonymous polymorphisms in melanocortin-4 receptor protect against obesity: the two facets of a Janus obesity gene

Abstract: The melanocortin-4 receptor (MC4R) gene pathogenic mutations are the most prevalent forms of monogenic obesity, responsible for approximately 2% of obesity cases, but its role in common obesity is still elusive. We analyzed the contribution of non-synonymous mutations V103I (rs2229616, c.307G > A) and I251L (no rs, c.751A > C) to obesity in 16 797 individuals of European origin from nine independent case-control, population-based and familial cohorts. We observed a consistent negative association of I251L vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
137
2
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(158 citation statements)
references
References 35 publications
14
137
2
5
Order By: Relevance
“…The functional implication of p.V103I in obesity is controversial since several case-control studies found similar 103Ile frequencies between extreme obese and nonobese individuals (Meyre et al, 2009). However, regarding the p.Ile251Leu variant, a meta-analysis conducted by Stutzmann et al (2007) showed a protective effect of the 251Leu allele: individuals carrying this allele have a reduced risk of obesity, nearly 50%, when compared with carriers of the wild-type allele (251Ile). Nevertheless, more studies are necessary to confirm if this polymorphism is or is not associated with BMI.…”
Section: Discussionmentioning
confidence: 99%
“…The functional implication of p.V103I in obesity is controversial since several case-control studies found similar 103Ile frequencies between extreme obese and nonobese individuals (Meyre et al, 2009). However, regarding the p.Ile251Leu variant, a meta-analysis conducted by Stutzmann et al (2007) showed a protective effect of the 251Leu allele: individuals carrying this allele have a reduced risk of obesity, nearly 50%, when compared with carriers of the wild-type allele (251Ile). Nevertheless, more studies are necessary to confirm if this polymorphism is or is not associated with BMI.…”
Section: Discussionmentioning
confidence: 99%
“…These associations were reproducible, using different eating pattern indicators both meaning excessive appetite. Given the effect of MC4R mutations on appetite 30,32,33 the risk of cumulating four false positive associations between MC4R rs17782313 and eating behaviour pattern out of five studies (using five different questionnaires) is unlikely. However our results need to be replicated in additional populations.…”
Section: Discussionmentioning
confidence: 99%
“…Only one of the 11 non-synonymous mutations (N62S) exhibited a reduced function, as indicated by a strongly reduced cell surface expression, and by signal transduction Table 2 MC4R functional assays MC4R cAMP accumulation and cell surface expression assays. Each amino acid replacement observed in the HGDP-CEPH panel is found in Table. Three sites (R7C, V103I, I251L) were not functionally tested in this study as these sites have been identiWed and assayed previously (Srinivasan et al 2004;Stutzmann et al 2007;Xiang et al 2006). Construct properties that did not result in an enhancement of intracellular cAMP levels (Table 2).…”
Section: Functional Characterization Of Non-synonymous Mutationsmentioning
confidence: 99%